Direct torque control of induction motor using Artificial Neural Network (ANN) / Fitra Kamil Abdul Halim - Abdul Halim, Fitra Kamil (2004)
This thesis present a direct torque control (DTC) using the space vector modulation technique which is applied to a three-phase inverter to control induction motor. The induction motor is modeled using space vector theory that describes the motor parameter in terms of d-axis and q-axis. The purposes of estimator or observer that represent the actual motor is to measure the flux and torque of the induction motor based on the current and voltages obtained from the induction motor. AI technique is implemented to replace the conventional Pi-controller and the outcome will be compared with the existing results in [4]. Simulation of the conventional and proposed controller will be presented as the final result.